Prognostic impact of MALs and potential immunotherapy targets in uveal melanoma - Jing Yang; Zhou Fu; Qin Xiang (Wiley, 2024)
Abstract Uveal melanoma (UM) is the most common primary ocular malignancy in adults, and the 5‐year disease‐related mortality rate is 30%. MAL proteolipid family (MALs), including T‐cell differentiation protein (MAL), T‐cell differentiation protein 2 (MAL2), and T‐cell differentiation protein like (MALL), were involved in the progression and prognosis of many different cancers. However, the role of MALs in UM was not reported. UM samples were extracted from The Cancer Genome Atlas. R software (R3.6.3) was used to comprehensively analyze the roles of the MALs (signiﬁcance threshold: p < 0.05). MALs mRNA expression was changed in UM tissues. In terms of tumor stage, MAL2 was highly expressed in T4 (p = 0.021). The ROC curves indicated that MAL2 and MALL were prognostic biomarkers for 1‐ and 3‐year survival in UM patients, and MAL2 also could predict 5‐year survival for UM patients. Then, the univariable and multivariable analysis showed that MAL2 and MALL were independent prognostic biomarkers. Next, we assessed the immune microenvironment of MALs in UM. MAL had no correlation with B7‐H3, but MAL2 and MALL had a positive correlation with B7‐H3. Our results revealed that the MAL proteolipid family may be prognostic biomarkers for UM patients and that B7‐H3 may be a novel immunotherapy target for UM.